Intentional power : the 6 essential leadership skills for triple bottom line impact - Stromberg, Lisen; Nichols, JeanAnn; Jones, Corey (Ascent Audio, 2023)
"Written by leadership experts Lisen Stromberg, JeanAnn Nichols, and Corey Jones, Intentional Power is a call to action for the next generation of leaders to move beyond an entirely individual focus toward a more sustainable approach to lead and succeed. Deeply researched, the authors draw on an extensive review of the latest literature and insights on leadership development, cognitive and positive psychology, organizational design, and performance management, as well as extensive interviews with leaders across several industries to highlight the most critical skills required by today's executives and managers. They offer a new model of leadership, the HEARTI® model, built on six core competencies: Humility, Empathy, Accountability, Resiliency, Transparency, and Inclusivity. These six leadership skills are essential for success in today's new world of work. You'll also find: a comprehensive, inclusive, and effective approach to leading organizations through the rest of the twenty-first century; examples from leaders across numerous industries who are driving impact for the teams, the companies, and the world at large; and practical ""How-To's"" and actionable Leader Tool Kit activities to help you learn and apply the skills discussed in the book."